2022
DOI: 10.1007/s13596-022-00670-2
|View full text |Cite
|
Sign up to set email alerts
|

Traditional herbal medicine: overview of research indexed in the scopus database

Abstract: Traditional herbal medicine has been playing an essential role in primary health care globally. The aim of this work is to present an overview of traditional herbal medicine research productivity over the past years. The data was accessed from the Scopus database ( www.scopus.com ), while VOSviewer.Var1.6.6, Bibliometrix, and R studio were used for further analysis of the obtained data. The results showed that researches on traditional herbal medicine increased annually after 1990, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…, 2023). Moreover, Scopus has been considered as a “World-leading scientific database” (Musa et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2023). Moreover, Scopus has been considered as a “World-leading scientific database” (Musa et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…It contains all the elements that are prerequisites for conducting a bibliometric analysis and has an enormous edge over other databases as it includes more social science literature (Farrukh et al, 2023). Moreover, Scopus has been considered as a "World-leading scientific database" (Musa et al, 2022).…”
Section: Selection Of Databasementioning
confidence: 99%
“…Among several pivotal databases like Scopus and Web of Science, Scopus was selected because it not only contains most of the journals covered by other relevant databases (i.e., having broad coverage) such as Web of Science (WoS) but also includes several journals not included in other databases (Herrera‐Franco et al, 2020; Mongeon & Paul‐Hus, 2016). Also, it has been considered a ‘ world‐leading scientific database ’ (Musa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of the population relying on traditional medicines in developing countries ranges from 60-80% (Ekor 2013, Sudha 2018, El Dahiyat et al 2020, Musa et al 2022. Research by Nyagumbo et al (2022) showed that medicinal plants and plant-derived medicines are widely used in peri-urban, rural and marginalized areas of Zimbabwe and they are becoming increasingly popular as natural alternatives to synthetic chemicals.…”
Section: Introductionmentioning
confidence: 99%